Note that y decreases by 5 when x increases by 1. So, start with
y = -5x
Now note that y(0) = -1, so you need to adjust the function a bit:
y = -5x-1
I need some help on this function rule question please.
8.) Find the function rule.
x: -2 -1 0 1 2
y: 9 4 -1 -6 -11
I'm having a really hard time figuring this out. Thanks to anyone that helps:)
4 answers
Anyone know how to help?
The function rules is:
y = -5x - 1
9 = -5(-2) - 1
4 = -5(-1) - 1
-1 = -5(0) - 1
-6 = -5(1) - 1
-11 = -5(2) - 1
y = -5x - 1
9 = -5(-2) - 1
4 = -5(-1) - 1
-1 = -5(0) - 1
-6 = -5(1) - 1
-11 = -5(2) - 1
Is this the right answer